2004
DOI: 10.1007/bf03033449
|View full text |Cite
|
Sign up to set email alerts
|

Binding of 4-(4-chlorophenyl)-1-[4-(4-fluorophenyl)-4-oxobutyl]pyridinium ion (HPP+), a metabolite of haloperidol, to synthetic melanin: Implications for the dopaminergic neurotoxicity of HPP+

Abstract: The toxicity of 4-(4-chlorophenyl)-1-[4-(4-fluorophenyl)-4-oxobutyl]pyridinium ion (HPP+), a metabolite of haloperidol, toward dopaminergic neurons was investigated. When HPP+ (approximately 100 microM) was added to primary cultures prepared from rat embryonic mesencephalon for 1 h, the survivability of dopaminergic neurons decreased significantly, and this effect was not inhibited by the dopamine transporter (DAT) inhibitor GBR 12909. In addition, HPP+ bound to neuromelanin, which is abundant in dopaminergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, HPP ϩ shows a moderate brain uptake index, which indicates that it may permeate the blood-brain barrier. These results support the hypothesis that HPP ϩ is formed mainly in the liver, circulates in the bloodstream, and enters the brain, where it induces damage to brain dopaminergic neurons (Kawashima et al, 2002(Kawashima et al, , 2004.…”
supporting
confidence: 86%
“…Furthermore, HPP ϩ shows a moderate brain uptake index, which indicates that it may permeate the blood-brain barrier. These results support the hypothesis that HPP ϩ is formed mainly in the liver, circulates in the bloodstream, and enters the brain, where it induces damage to brain dopaminergic neurons (Kawashima et al, 2002(Kawashima et al, , 2004.…”
supporting
confidence: 86%
“…After short (30 min) [ 3 H]haloperidol incubation with either human brain SN or superior cerebellar peduncle homogenates in vitro, centrifugation revealed that about twice as much haloperidol bound to pigmented bands (containing NM) from SN than non-pigmented bands from superior cerebellar peduncle (similar results were obtained for [ 3 H]imipramine and [ 3 H]chlorpromazine) [ 106 ]. Haloperidol can undergo biotransformation into 4-(4-chlorophenyl)-1-[4-(4-fluorophenyl)-4-oxobutyl]pyridinium ion (HPP + , resembling MPP + ) which bound to synthetic melanin in a reversible manner [ 111 ]. HPP + damaged rat embryonic primary cultured dopaminergic neurons [ 111 ], but which does not demonstrate NM involvement of toxicity (young cultured cells are considered not to have NM)).…”
Section: Known Nm-binding Metals and Chemicalsmentioning
confidence: 99%
“…Haloperidol can undergo biotransformation into 4-(4-chlorophenyl)-1-[4-(4-fluorophenyl)-4-oxobutyl]pyridinium ion (HPP + , resembling MPP + ) which bound to synthetic melanin in a reversible manner [ 111 ]. HPP + damaged rat embryonic primary cultured dopaminergic neurons [ 111 ], but which does not demonstrate NM involvement of toxicity (young cultured cells are considered not to have NM)). HPP + was moderately taken up into brains of rats [ 112 ].…”
Section: Known Nm-binding Metals and Chemicalsmentioning
confidence: 99%
“…Thiols also release iron from monoferrictransferrin (Baldwin et al, 1990). Recently, it was found that binding of the haloperidol metabolite 4-(4-chlorophenyl)-1-[4-(4-fluorophenyl)-4-oxobutyl]pyridinium ion (HPP + ), which chemically resembles MPP + , to melanin had a major influence of HPP + -induced neurotoxicity to primary cultures of rat embryonic mesencephalon (Kawashima et al, 2004). A new mechanism for iron neurotoxicity has been reported, since iron toxicity is dependent on (i) Fedopamine complex formation, (ii) uptake through the monoaminergic transporter, and (iii) inhibition of DTdiaphorase by dicoumarol.…”
Section: Heavy Metal Neurotoxins Ironmentioning
confidence: 99%